Dark day in the deep sea - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series. Merlin missions, 2017)
Eight-year-old Jack and his seven-year-old sister, Annie, learn about the ocean, solve the mystery of its fabled sea monster, and gain compassion for their fellow creatures after joining a group of nineteenth-century explorers aboard the H.M.S. "Challenger."